The S100 calcium-binding protein A4 level is elevated in the lungs of patients with idiopathic pulmonary fibrosis. (September 2020) - Lee, Jong-Uk; Chang, Hun Soo; Shim, Eun-Young; Park, Jai-Seong; Koh, Eun-Suk; Shin, Hwa-Kyun; Park, Jong-Sook; Park, Choon-Sik
Abstract: Background: Fibroblast dysfunction is the main pathogenic mechanism of idiopathic pulmonary fibrosis (IPF). S100 calcium-binding protein A4 (S100A4) plays critical roles in the proliferation of fibroblasts and in the development of pulmonary, hepatic, and renal fibrosis. However, the clinical implications of S100A4 in IPF have not been evaluated. Methods and materials: The S100A4 mRNA and protein levels were measured by real-time PCR and immunoblotting in fibroblasts from IPF patients and controls. The S100A4 level was measured by enzyme-linked immunosorbent assay in bronchoalveolar lavage fluid (BALF) from the normal controls (NCs; n = 33) and from patients with IPF (n = 87), non-specific interstitial pneumonia (NSIP; n = 22), hypersensitivity pneumonitis (HP; n = 19), and sarcoidosis (n = 9). S100A4 localization was evaluated by immunofluorescence staining. Results: The S100A4 mRNA and protein levels were significantly higher in fibroblasts from IPF patients (n = 14) than in those from controls (n = 10, p < 0.001). The S100A4 protein level in BALF was significantly higher in the IPF (89.25 [49.92–203.02 pg/mL]), NSIP (74.53 [41.88–131.45 pg/mL]), HP (222.36 [104.92–436.92 pg/mL]) and sarcoidosis (101.62 [59.36–300.62 pg/mL]) patients than in the NCs (7.57 [1.31–14.04 pg/mL], p < 0.01, respectively). Cutoff S100A4 levels of 18.85 and 28.88 pg/mL had 87.4% and 87.8% accuracy, respectively, for discriminating IPF and other lung diseases from NCs. Conclusions: S100A4 is expressed by α-SMA-positive cells in the interstitium of the IPF patients. S100A4 may participate in the development of IPF, and its protein level may be a candidate diagnostic and therapeutic marker for IPF. Highlights: S100A4 level was significantly higher in the BALF of patients with IPF. S100A4 offered a good diagnostic accuracy with high specificity and sensitivity for differentiating IPF from NC. S100A4 was mainly expressed by α-SMA-positive fibroblasts in the IPF- lung.